Immigration Policy Reform in the United States: Reframing the enforcement discourse to fight human trafficking and promote shared prosperity - Avendaño, Ana; Fanning, Charlie (Anti-Trafficking Review, 2013)
At the time of this writing, the United States Senate has passed the Border Security, Economic Opportunity, and Immigration Modernization Act (S. 744). The bill is the product of countless political compromises and would significantly transform the U.S. immigration system. This paper explores shortcomings in U.S. immigration policy, deconstructs provisions in the bill, and makes policy proposals that would protect and empower migrants who interface with the U.S. immigration system in dangerous and under-regulated environments at the border and in sending communities, in labour recruitment networks, and in the U.S. workforce. Ultimately, the paper seeks to continue an ongoing conversation that challenges the criminalisation of migration which perpetuates vulnerability, and instead forwards rights-based policies that would promote shared prosperity.